Development of Sustainable Fashion Soft Skills by Fashion Educationists Through Non-Formal Education Programs - Evania Yessica; Tri Siwi Agustina; Eka Mega Pertiwi; Rohmatuz Zuhroh Sofwani (Faculty of Education Universitas Negeri Malang, 2025)
This research aims to discuss the development of students' soft skills in achieving fashion sustainability taught by fashion educators and to explore the materials applied in fashion education institutions. Fashion is one of the primary human needs that provides self-identity, boosts self-confidence, offers comfort, and upholds values of modesty. Consequently, the fast fashion industry competes to produce clothing on a large scale, often unaware of the negative impacts such as pre-consumption and post-consumption waste, which harm the environment and threaten human well-being. Therefore, the term sustainable fashion has emerged, referring to environmentally friendly clothing. In response, non-formal fashion education institutions have taken the initiative to teach materials related to soft skills aimed at fashion sustainability, including the development of leadership character, ethical fashion, skills in designing sustainable fashion garments, and fashion business. This study employs a descriptive qualitative research method, with data collected through in-depth interviews and observations of fashion educationists. Through the programs and materials provided to students, this scientific research is expected to benefit related human resources and raise awareness about preserving the environment through clothing.